CLINICO-HAEMATOLOGIC PARAMETERS AND ASSESSMENT OF POST-INDUCTION STATUS IN ACUTE LYMPHOBLASTIC LEUKEMIA - Niaz, Hina; Hamid Saeed Malik; Rafia Mahmood; Asad Mehmood; Sara Ali Zaidi; Ummarah Bilal (Journal of Ayub Medical College Abbottabad, 2022)
Background: Acute Leukaemia is a malignant disorder characterized by an abnormal proliferation of immature cells, called blasts. Classically, acute leukaemia is classified into acute myeloid leukaemia and acute lymphoblastic leukaemia depending on the lineage of the immature cells. Objective of the study was to evaluate the clinical presentations, analyze the haematologic parameters at time of diagnosis and assess the post-induction status in newly diagnosed ALL patients. This cross-sectional study was conducted in the Department of Haematology, Armed Forces Institute of Pathology, Rawalpindi from June to November 2019. Methods: A total of 55 newly diagnosed ALL patients were recruited including children, adults and elderly. Detailed medical history and physical findings were noted. Haematologic parameters were documented. Each patient was treated as per standard protocol and remission induction status was determined on day 29 of treatment. Results: The median age of the study cohort of 55 newly diagnosed ALL patients was 8.5 years. Males were 37 (67.3%) and females were 18 (32.7%) with a male to female ratio of 2:1. Paediatric group included 31 (56.4%) patients. Nine (16.4%) patients were in the adult group and 15 (27.3%) in the elderly age group. The time from onset of symptoms to diagnosis of acute lymphoblastic leukaemia was 98.87±79.21 days. Fever was the most common symptom but body aches were common among paediatric group while pallor was the most common sign. Mean WBC was 29.1±27.9 x109/l, Hb was 8.1±2.9 g/dl and platelet count was 60±41.8 x109/l B-acute lymphoblastic leukaemia was more common than T-acute lymphoblastic leukaemia. A total of 52 patients were assessed on day 29 to evaluate for post-induction remission status. The remission rate of our cohort of patients was 82.7%. Conclusion: Most of the patients were in paediatric age group and remission rate was better in this age group compared to elderly population. B-ALL was associated with good response to induction chemotherapy while patients with BCR-ABL1 gene rearrangement did not respond well to treatment. Identification of prognostic features at diagnosis will further help our clinicians to predict outcomes of the disease.